The Effect of Digital Literacy, Market Orientation, and Digital Marketing Capability on MSME Marketing Performance - Harianto Harianto; Ramlah Puji Astuti; Soesanty Maulany (CV. AFDIFAL MAJU BERKAH, 2026)
This study explores how digital literacy, market orientation, and digital marketing capability affect the marketing performance of Food and Beverage MSMEs in Cirebon Regency. A quantitative method utilizing an associative research design was used to investigate the connections between the variables. The research included 100 MSME owners chosen via simple random sampling utilizing Slovin’s formula with a 10% margin of error. Data were collected using a structured questionnaire that utilized a five-point Likert scale and were analyzed via multiple linear regression with IBM SPSS software. The results demonstrate that digital literacy greatly improves marketing performance and stands out as the most impactful factor among the variables analyzed. Moreover, both market orientation and digital marketing capability show positive and substantial impacts on marketing performance. At the same time, the three variables together have a notable impact on the marketing performance of Food and Beverage MSMEs. These findings indicate that enhancing digital skills, refining market-driven business practices, and building digital marketing abilities are crucial strategies for boosting the competitiveness and marketing efficiency of MSMEs in a progressively digital business landscape